2023
DOI: 10.3390/jcm12041465
|View full text |Cite
|
Sign up to set email alerts
|

Refraining from Packed Red Blood Cells in Cardiopulmonary Bypass Priming as a Method of Neuroprotection in Pediatric Cardiac Surgery

Abstract: Congenital heart defect (CHD) surgeries are performed with cardiopulmonary bypass (CPB) and are complicated by several factors that affect the child’s brain. However, to date, the number of studies on brain protection in cardiac surgery remains small. The aim of this study was to assess the impact of refraining from using packed red blood cells (PRBCs) in priming solutions in children with congenital defects (CHDs) who require surgical interventions using CPB to prevent brain injury in the postoperative period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…In our previous investigation, we showed SIRS and cerebral damage markers dynamics during cardiac surgery in children with same including criteria [21].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In our previous investigation, we showed SIRS and cerebral damage markers dynamics during cardiac surgery in children with same including criteria [21].…”
Section: Discussionmentioning
confidence: 93%
“…In our previous research, we showed the SIRS and cerebral damage changings markers during the correction of CHD among children with similar inclusion criteria [21].…”
Section: Discussionmentioning
confidence: 95%